Eesti ühiskond kiirenevas ajas = Estonian society in an accelerating time Uuringu "Mina. Maailm. Meedia" 2002-2014 tulemused = Findings of the survey "Me. The World. The Media" 2002-2014 - Vihalemm, Peeter; Lauristin, Marju; Kalmus, Veronika; Vihalemm, Triin (University of Tartu Press, 2017)
The book examines the transformation of the life-world in the context of the rapidly changing Estonian society. The authors pose three main questions to be discussed throughout the book: What has happened in the Estonian society during the last decade? How to describe the present society? Who shapes the social developments and in which direction? The authors formulate three main theses: (1) the great transformation occurring on the macro level is reflected in the life-world as changes in the temporal and spatial dimensions and the multiplicity of individuals' social identifications in the context of new opportunities. This brings about social and cultural fragmentation of the society and a clear differentiation and polarisation of mental structures; (2) the inherently conflictual nature of transformation is expressed in socially differentiating self-positioning, dependent on the resources individuals possess for coping with changes, and leading to the re-stratification of the society (re-structuration); (3) the acceleration of social and personal time and the opening of social space, on one hand, and social stratification, on the other hand, perform as mutual amplifiers. The authors conclude that the first wave of transitional controversies between more and less capitalised social groups is receding due to increasing general welfare. At the same time, global technological and cultural changes, migration crises, and increasing violence and terrorism have brought about new controversies and challenges in Estonian society.